Odd hours [compact disc, unabridged] - Koontz, Dean R. (Dean Ray), 1945- (Koontz, Dean R. (Dean Ray), 1945- Odd Thomas novel., 2008)
In the obscure little town of Pico Mundo, California, a fry cook named Odd Thomas was rumored to have the ability to communicate with the dead. Word of Odd's gifts filtered far beyond Pico Mundo, attracting unforgettable new friends, and enemies of implacable evil.